A Field Experience Program for Teaching Children with Diverse Abilities Course in A Faculty of Education - Zendrato, Juniriang (Jurnal Basicedu, 2021)
This article discussed the gap between the Graduate Profile and the assessment of the Teaching Children With Diverse Abilities course held by the Faculty of Education in Tangerang, Indonesia. Therefore, the purpose of the paper was to explain the importance of a field experience program for the course as a solution to achieve the Graduate Profile. It is a qualitative research method. A case study was employed. The results were the field experience program could be implemented in this course because of (1) preparing the teacher students to teach special needs children; (2) building partnership with schools to be teaching practice places for the teacher students; (3) giving opportunities to teacher students to improve their teaching skills and develop their teaching affection, and (4) increasing the teacher students' feeling of competency. Moreover, the program did not only guide the teacher students to understand inclusive education, but also the holistic education from the Christian perspective. Therefore, the teacher students needed to have transcendental relationships before teaching the students with diverse abilities. The conclusion was the field experience program in the Teaching Children With Diverse Abilities fulfilled the graduate profile in the values of â€œCallingâ€ and â€œCompetenceâ€ through its achievement to Faculty of Education Program Learning Objectives, Competencies Learning Objectives, and assessments.